High Burden of Subclinical Cardiovascular Target Organ Damage After Pediatric Liver Transplantation. Issue 5 (25th March 2019) - Memaran, Nima; Borchert‐Mörlins, Bianca; Schmidt, Bernhard M. W.; Sugianto, Rizky I.; Wilke, Hannes; Blöte, Ricarda; Baumann, Ulrich; Bauer, Elena; von Wick, Anika; Junge, Norman; Leiskau, Christoph; Pfister, Eva D.; et al.
Abstract : Cardiovascular (CV) events account for 8%‐13% of deaths after liver transplantation (LT) in adulthood. Although CV risk factors (RFs) are present, little is known about the prevalence of subclinical CV target organ damage (TOD) in children after LT. The aim of this prospective observational study was to assess the prevalence of subclinical CV TOD in children after LT and to identify RFs contributing to CV damage as potential targets for clinical intervention. In this study, 104 children after LT (54% female, 46% male; aged 11.5 ± 3.8 years) underwent cross‐sectional assessment of subclinical TOD by carotid‐femoral pulse wave velocity (PWV), carotid intima‐media thickness (IMT), and left ventricular mass index (LVMI). Results were correlated with the presence of CV RFs (obesity, hypertension, dyslipidemia, renal impairment, anemia, and microinflammation). Of the patients, 22% were exposed to 2 CV RFs, and 36% displayed 3 or more CV RFs. Pathological results for PWV, IMT, and LVMI were found in 21.9%, 57.0%, and 11.1% of patients, respectively. In the multivariate analysis, diastolic blood pressure ( P  = 0.01) and estimated glomerular filtration rate (eGFR; P  = 0.03) were independently associated with PWV, eGFR ( P  = 0.005), and age at LT ( P  = 0.048) with IMT and body mass index with LVMI ( P  = 0.004). In conclusion, patients after pediatric LT carry a substantial burden of subclinical CV TOD. Identification of modifiable CV RFs opens opportunities for targeted intervention in order to reduce CV morbidity and mortality in the future.